Risk Factors for Preeclampsia in the Working Area of Martapura 1 Health Center, Banjar Regency - Fatimah, Husnul; Noor, Meitria Syahadatina; Sauqi, Hardyan; Husaini, Husaini; Suhartono, Eko (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Preeclampsia is characterized by hypertension accompanied by proteinuria or edema, typically occurring after 20 weeks of gestation until the end of the first postpartum week. It remains one of the top five causes of maternal mortality. According to data from Martapura 1 Community Health Center, 45 cases of preeclampsia were reported from 1,245 examined pregnant women between January and July 2023. This study aimed to identify the risk factors associated with preeclampsia among pregnant women in this area. Using an analytical observational method with a cross-sectional design, the study was conducted in October–November 2023 and involved 102 respondents selected via cluster random sampling. Data collection utilized questionnaires and maternal health books. Statistical analysis revealed significant associations between maternal age and preeclampsia (p = 0.011), and between chronic energy deficiency (CED) and preeclampsia (p = 0.021). However, family history (p = 0.371), diabetes mellitus, quality of health services, and antenatal care interest were not significantly associated. The latter variables were analyzed descriptively due to test limitations. The study concluded that maternal age and CED are significantly associated with preeclampsia, with maternal age being the most dominant factor.